Correlation of Stature of Adult Bangladeshis with the Length of Clavicle-A Radiographic Approach - Islam, Tahmina; Ara, Shamim; Kamal, AHM Mostafa; Kawser, Tunajina; Ferdous, Jannatul (Bangladesh Journal of Anatomy, 2020)
Context: Clavicle provides an opportunity for estimating stature of an unknown individual. Methods: This study was a cross sectional study carried out in the Department of Anatomy, Dhaka Medical College, Dhaka from January, 2015 to December, 2015. Adult males and females attending the Radiology and Imaging Department of Dhaka Medical College and Hospital (DMCH), for the chest radiograph advised by their physicians were the subjects of the study. Height of the subject was taken using stadiometer. One hundred radiographs of left clavicle (posterior-anterior view) were taken of which fifty (50) were of males and fifty (50) were of females. The radiographs of clavicles were viewed on the x-ray view box and traced on the transparent sheets. Length of clavicles were measured in mm from the radiographs. Heights of adult males and females were calculated using the length of clavicle. Results: No significant difference (P>0.05) was found while comparing measured height of adult male with the calculated height of adult male using length of clavicle. No significant difference (P>0.05) was found while comparing measured height of adult female with the calculated height of adult female using length of clavicle. Conclusions: Present study showed that stature of adult male and female can be calculated using length of clavicle. Bangladesh Journal of Anatomy July 2020, Vol. 18, No. 2, pp. 36-40